2018
DOI: 10.3889/oamjms.2018.355
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of P38 Mitogen-Activated Protein Kinase Expression to Clinical Stage in Nasopharyngeal Carcinoma

Abstract: BACKGROUND:Nasopharyngeal carcinoma (NPC) is uncommon and usually diagnosed at the advanced stage. A subfamily of mitogen-activated protein kinase which is called p38 mitogen-activated protein kinase (MAPK) involved in response to stress, and plays an important role in cell regulation. There is a suggestion that p38 mitogen-activated protein kinase could be a potential biomarker to determine the clinical stage of nasopharyngeal carcinoma.AIM:The aim of this study is for observing and analysing the correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…As mentioned in Tables 1 and 2, increased expression of p38 MAPKs and JNKs has also been reported in NPC [59,78]. JNK and p38 MAPK activities have been evaluated in treatment-resistant NPC, of which the protein expressions of both JNK and p38 MAPK were found to be higher in cetuximab-resistant NPC [81].…”
Section: Jnk and P38 Mapk Activities Inhibit Pro-apoptotic Signaling ...mentioning
confidence: 91%
“…As mentioned in Tables 1 and 2, increased expression of p38 MAPKs and JNKs has also been reported in NPC [59,78]. JNK and p38 MAPK activities have been evaluated in treatment-resistant NPC, of which the protein expressions of both JNK and p38 MAPK were found to be higher in cetuximab-resistant NPC [81].…”
Section: Jnk and P38 Mapk Activities Inhibit Pro-apoptotic Signaling ...mentioning
confidence: 91%
“…In particular, MAPK demonstrated strong associations in our analysis. In fact, we found that many MAPK-associated signaling components were upregulated in NPC samples while SB203580, a small molecule MAPK inhibitor, was predicted to be inhibited; activity of these factors are known mediators of NPC tumorigenesis [56]. Specifically, SB203580 has been shown to down-regulate the p38 MAPK pathway, resulting in MMP-2 inhibition, another protein important for extracellular matrix breakdown, ultimately limiting NPC invasion [57,58].…”
Section: Plos Onementioning
confidence: 95%
“…Like other MAPKs, the functions of p38 have been well-established in tumor cells, directing any number of cell processes including differentiation, migration, and inflammation [58]. Accordingly, p38 overexpression is associated with poor responses to conventional therapy in several cancers including breast cancer, nasopharyngeal carcinoma, gastric, and pancreatic cancer [59][60][61][62].…”
Section: P38 Mapk Inhibitionmentioning
confidence: 99%